Pengembangan Aplikasi E-Marketplace Undangan berbasis Web - Inas Nabila; Fajar Pradana; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Invitations are one of the most crucial needs in an event that is used to invite people and groups, where invitations can be made in printed or digital form. Print invitations, currently the difficulty of finding and comparing prices at each printing service is one of the shortcomings of making printed invitation designs. As many as 86 percent of Indonesian internet users shop online via any device. This figure is obtained from data compiled by the Global Web Index summarized by We Are Social and Hootsuite (CNN, 2019). Therefore, a design application was created as an invitation-making medium and a printing partner marketplace that provides invitation printing services according to user needs. This application facilitates the transaction process between consumers and printing partners as a third party. Consumers can design invitations as desired and choose to continue to be printed through the printing services available in the system. Payment can be made online and the invitation will be sent by the printer to the buyer's address. This invitation e-marketplace application was built using the Software Engineering approach by using the Waterfall System Development Life Cycle method which consists of requirements analysis, system design, system implementation, and system testing. The results of the waterfall method produce 34 functional requirements and 1 non-functional requirement with 4 actors as system users, namely guest, member, partner, and admin. Implemented using the CodeIgniter framework with the PHP programming language supported by HTML, CSS, Javascript, Bootstrap, and supported by 2 APIs, namely Fabric.js and RajaOngkir. The tests were carried out by testing white box, black box, and usability testing using the SUS (System Usability Scale) which has an average final score of 82 which is considered acceptable.